Targeting breast cancer detection with military technology. - Irvine, J.M (IEEE Engineering in medicine and biology magazine)
Discusses the applicability of automated target recognition technology (ATR) to early screening for breast cancer. An overview of ATR technology is given and parallels to the cancer screening problem are given. Recommendations for future investigation are given.